Effect of demulsification on cationicsurfactant-stabilized oil-in-water emulsion using Graphene Oxide - Yahya, Muhammad Ikhmal (2018)
Graphene oxide (GO) is an amphiphilic material capable of breaking oil-in-water emulsion at room temperature. In the oil and gas industry, emulsions formation in the pipeline is a problem as emulsion will have negative effects or problems to the processing plant. The existence of emulsions in the crude oil will reduce the quality of the crude oil itself, increase the cost of operating due to emulsion separation as well as causing corrosion problem to the flowlines and transport system. Chemical demulsification are widely being used in the industry to treat oil-in-water emulsion which involves the use of chemical additives to rapidly enhance the emulsion breakdown process. Hummer's method was used and successfully synthesized graphene oxide from graphite powder through strong oxidation process. Characterization of the GO produced was done using FTIR and XRD. Result shows various functional groups peaks produced in the graphene oxide in comparison with the originally used graphite powder. The XRD test also produced positive result as it gives similar result of 2θ = 10.26̊ in theory. The performance of GO on separation of cationic surfactant stabilized emulsion was assessed experimentally. Results shows that GO successfully improves the demulsification process even under acidic condition but had a decrease in performance under alkaline condition.